Reconceptualizing CSR Grant Governance in Regional SOEs: Integrating Maqasid al-Shariah and SDG 17 - Dita Kurniawati; Joni Emirzon; Putu Samawati; Saifudin Amin (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to reconceptualize grant arrangements by BUMDs in CSR programs through a beneficiality principle approach aligned with the Sustainable Development Goals (SDGs), particularly SDG 17 on partnerships for sustainable development. The focus is on formulating recommendations for regulatory concepts that can be applied in the future. This goal is directed to increase legal certainty and the social impact of CSR programs. Theoretical framework: The theoretical framework is based on the concept of regulating BUMD's CSR obligations based on the applicable legal basis while incorporating SDGs principles. The principle of the usefulness approach is used as the basis for the analysis of regulatory reconstruction, including the integration of the perspective of maqasid al-shari'ah and SDG 17. The framework emphasizes a balance between legal certainty, public benefit, sustainability, and collaborative governance. Literature review: The literature review covers social and environmental responsibility regulations and the concept of grants in BUMD CSR, including the need to reconstruct regulations so that they do not overlap with APBD grants, while supporting SDGs-oriented governance. Methods: The method used is normative juridical through the study of legal literature, laws, and regulations to analyze problems and formulate regulatory concepts in line with SDGs values. Results: The results show that there is no clear legal terminology for grants by BUMDs, so that it has the potential to cause inequality with APBD grants and needs to be based on the principle of sustainable utility and SDGs-oriented governance, particularly strengthening partnerships (SDG 17). Implications: This study emphasizes the importance of clear regulations to increase the accountability of BUMD CSR and ensure tangible social benefits for the community while contributing to the achievement of SDGs. Novelty: The novelty lies in the formulation of the CSR concept through BUMD grants based on the principles of usefulness, maqasid al-shari'ah, and SDGs (especially SDG 17), while still paying attention to legal certainty and sustainable development.